Spatial‐Temporal Behaviors of Large‐Scale Ionospheric Perturbations During Severe Geomagnetic Storms on September 7–8 2017 Using the GNSS, SWARM and TIE‐GCM Techniques. Issue 3 (16th March 2022) - Li, Wang; Zhao, Dongsheng; He, Changyong; Hancock, Craig M.; Shen, Yi; Zhang, Kefei
Abstract: Geomagnetic storms on 7–8 September 2017 triggered severe ionospheric disturbances that had a serious effect on satellite navigation and radio communication. Multiple observations derived from Global Navigation Satellite System receivers, Earth's Magnetic Field and Environment Explorers (SWARM) and the Thermosphere‐Ionosphere ‐Electrodynamics General Circulation Model's simulations are utilized to investigate the spatial‐temporal ionospheric behaviors under storm conditions. The results indicate that the electron density in the Asia‐Australia, Europe‐Africa and America sectors suddenly changed with the Bz southward excursion, and the ionosphere over low‐middle latitudes under the sunlit hemisphere is easily affected by the disturbed magnetic field. The SWARM observations verified the remarkable double‐peak structure of plasma enhancements over the equator and middle latitudes. The physical mechanism of low‐middle plasma disturbances can be explained by a combination effect of equatorial electrojets, vertical E × B drifts, meridional wind and thermospheric O/N2 change. Besides, the severe storms triggered strong Polar plasma disturbances on both dayside and nightside hemispheres, and the Polar disturbances had a latitudinal excursion associated with the offset of geomagnetic field. Remarkable plasma enhancements at the altitudes of 100–160 km were also observed in the auroral zone and middle latitudes (>47.5°N/S). The topside polar ionospheric plasma enhancements were dominated by the O+ ions. Furthermore, the TIE‐GCM's simulations indicate that the enhanced vertical E × B drifts, cross polar cap potential and Joule heating play an important role in generating the topside plasma perturbations. Key Points: Positive disturbances over low‐middle latitudes only appear on the dayside, but polar disturbances occur on both dayside and nightside Storms trigger bottomside plasma enhancements over middle‐high latitudes (>47.5 N/S) that have a latitudinal offset with geomagnetic field A combination of equatorial electrojet, E × B drifts, meridional wind and O/N2 change is responsible for low‐middle latitudinal disturbances